Safety and Efficacy of High-Dose Vitamin B6 as an Adjunctive Treatment for Antipsychotic-Induced Hyperprolactinemia in Male Patients With Treatment-Resistant Schizophrenia - Zhuo, Chuanjun; Xu, Yong; Wang, Haibo; Fang, Tao; Chen, Jiayue; Zhou, Chunhua; Li, Qianchen; Liu, Jie; Xu, Shuli; Yao, Cong; Yang, Weiliang; Yang, Anqu; et al. (Frontiers in Psychiatry, 2021)
This study aimed to investigate the safety and efficacy of high-dose vitamin B6 (vB6) as an adjunct treatment for antipsychotic-induced hyperprolactinemia (AIHP) in male patients with treatment-resistant schizophrenia (TRS). In this randomized double-blinded controlled study, patients were randomized (1:1) into a control group given aripiprazole (ARI; 10 mg/day; n=100) or an intervention group given vB6 (300 mg/12 h for 16 weeks; n=100). Prolactin levels, psychotic symptoms [Positive and Negative Syndrome Scale (PANSS)], cognitive function [MATRICS Consensus Cognitive Battery (MCCB)], liver function, kidney function, growth hormone level, micronutrient levels, blood lipids, and adverse secondary effects (ASEs)[Treatment Emergent Symptom Scale (TESS) and Barnes-Akathisia scale] were monitored. After a 16-week treatment period, the vB6 group showed a 68.1% reduction in serum prolactin levels (from 95.52 ± 6.30 μg/L to 30.43 ± 18.65 μg/L) while the ARI group showed only a 37.4% reduction (from 89.07 ± 3.59 μg/L to 55.78 ± 7.39 μg/L). During weeks 1–4, both treatments reduced prolactin similarly. Subsequently, the ARI effect plateaued, while the vB6 effect remained robust. The vB6 group showed better alleviation of psychotic symptoms and cognitive impairment. No serious ASEs were observed; ASEs were more frequent in the ARI group. AIHP reduction efficacy of vB6 was associated with baseline prolactin and triglyceride levels, total vB6 dosage, and education level. In conclusion, compared with the ARI group, TRS patients given vB6 showed better attenuation of AIHP, lower ASE scores, and greater improvements in clinical symptoms and cognitive impairments. These results support further consideration of vB6 as a putative treatment for AIHP.